2020
DOI: 10.20945/2359-3997000000318
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and obesity: the meeting of two pandemics

Abstract: COVID-19 and obesity are two pandemic diseases that the world is currently facing. Both activate the immune system and mediate inflammation. A sequence of disease phases in patients with severe COVID-19 results in a cytokine storm, which amplifies the subclinical inflammation that already exists in patients with obesity. Pro-inflammatory cytokines and chemotactic factors increase insulin resistance in obesity. Therefore, a greater systemic inflammatory response is establishe, along with an increased risk of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
1
8
0
1
Order By: Relevance
“…According to the World Health Organization (WHO), between 1975 and 2016, the number of people with obesity in the world almost tripled, which means approximately 13% of the world’s adult population (11% of men and 15% of women) were people with obesity in 2016. This fact leads the WHO to consider obesity as the global epidemic of the 21st century [ 1 ], even above the current COVID-19 pandemic [ 2 ]. Particularly, people with overweight and obesity are closely associated with the development of hypertension, cardiovascular disease, diabetes, dyslipidemia, and some types of cancer, among other diseases and comorbidities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), between 1975 and 2016, the number of people with obesity in the world almost tripled, which means approximately 13% of the world’s adult population (11% of men and 15% of women) were people with obesity in 2016. This fact leads the WHO to consider obesity as the global epidemic of the 21st century [ 1 ], even above the current COVID-19 pandemic [ 2 ]. Particularly, people with overweight and obesity are closely associated with the development of hypertension, cardiovascular disease, diabetes, dyslipidemia, and some types of cancer, among other diseases and comorbidities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This change in profile may result from improved reporting, with a consequent decrease in missing data. Perhaps scientific evidence indicating the importance of these comorbidities in influencing the severe form of COVID-19 ( 42 - 43 ) encouraged improved reporting.…”
Section: Discussionmentioning
confidence: 99%
“…38 Immune dysregulation, which tends to occur in obese individuals affected by COVID-19, may be related to a phenomenon known as hypercytokinemia or "cytokine storm. " 39 However, Brandão et al 40 have indicated that the initial immune response is very weak considering the high SARS-CoV-2 viral load, which justifies the excessive recruitment of cytokines. This mechanism of action is aggravated by viral overload in epithelial cells, especially in the lungs, causing the collapse of these structures.…”
Section: Obesity and Covid-19mentioning
confidence: 99%